Beyond the rare: a case of pseudomyogenic hemangioendothelioma treated sequentially with everolimus, denosumab, and pazopanib - Douglas Dias e Silva; Camila Bobato Lara Gismondi; Murilo Marques Almeida Silva; Renee Zon Filipi; Fernando Moura; Reynaldo Jesus-Garcia; Roberto Carmagnani Pestana (Einstein (São Paulo))
ABSTRACT Pseudomyogenic hemangioendothelioma is an ultra-rare vascular sarcoma that most commonly affects young adults, with a male predominance. It is diagnosed using a combination of imaging studies, histopathological examinations, and immunohistochemical staining. Surgical excision is the mainstay of treatment for pseudomyogenic hemangioendothelioma, with the goal of achieving a wide local excision and reducing the risk of recurrence. The role of systemic therapies is not well established because of the rarity of pseudomyogenic hemangioendothelioma, uncertainty regarding its response to currently approved medications, and lack of randomized controlled trials. We describe the case of an 18-year-old male patient diagnosed with multifocal pseudomyogenic hemangioendothelioma of the left lower limb who was treated with everolimus in addition to denosumab, achieving a partial response that was consolidated with resection, radiofrequency ablation, and radiotherapy of multiple local lesions, achieving a long-lasting response. Following subsequent disease progression, the patient responded favorably to pazopanib, with no significant toxicities.